Foreign body aspiration in children: Treatment timing and related complications. (May 2021) - Antón-Pacheco, Juan L.; Martín-Alelú, Rubén; López, María; Morante, Rocío; Merino-Mateo, Lara; Barrero, Sergio; Castilla, Rubén; Cano, Indalecio; García, Araceli; Gómez, Andrés; Luna-Paredes, M Carmen
Abstract: Background/purpose: The aims of this study were to describe our experience in the management of FB aspiration in children, focusing on the eventual association between delay in treatment and the development of complications, and to determine if the incidence of this emergency had decreased in the last 10 years. Methods: Retrospective study of children with a diagnosis of FB aspiration managed between 1999 and 2019 at a tertiary care referral hospital. The following data were collected: demographics, clinical presentation, radiological findings, endoscopic technique, type of FB, time elapsed between the aspiration episode and treatment, and complications. Main outcome measures were the rate of complications (intraoperative and long-term) in the cohort of patients with delay in treatment (>72 h), and the incidence of FB aspiration in each of the two historical subgroups of the study. Results: The study included 130 patients, 66.2% male, with a median age of 24 months. Cough was the most frequent symptom (76.1%) and unilateral air trapping was the most common radiological finding (48.8%). Removal of FB was performed with rigid bronchoscopy in every case. The most common type of FB was organic (73%) and located in the right bronchial system (47.7%). The global rate of complications was 16.1%. Patients with a delay in treatment beyond 72 h from the aspiration episode showed a statistically significant risk of developing both intraoperative and postoperative complications. Additionally, we have stated that the incidence of FB aspiration in our community has decreased by 44.4% in the last 10 years. Conclusions: The incidence of FB aspiration has remarkably decreased in our environment in the last decade. Delay in treatment placed our patients at a significant higher risk of developing complications both during the bronchoscopic procedure and in the long-term. Highlights: The incidence of foreign body aspiration in children has decreased in our environment in the last decade. Delay in treatment placed our patients at a significant higher risk of developing complications. Rigid bronchoscopy is the procedure of choice when dealing with foreign body aspiration in children.